2016
DOI: 10.3390/toxins8060159
|View full text |Cite
|
Sign up to set email alerts
|

Early Genotoxic and Cytotoxic Effects of the Toxic Dinoflagellate Prorocentrum lima in the Mussel Mytilus galloprovincialis

Abstract: Okadaic acid (OA) and dinophysistoxins (DTXs) are the main toxins responsible for diarrhetic shellfish poisoning (DSP) intoxications during harmful algal blooms (HABs). Although the genotoxic and cytotoxic responses to OA have been evaluated in vitro, the in vivo effects of these toxins have not yet been fully explored. The present work fills this gap by evaluating the in vivo effects of the exposure to the DSP-toxin-producing dinoflagellate Prorocentrum lima during the simulation of an early HAB episode in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 42 publications
1
17
0
Order By: Relevance
“…The observed levels of DNA strand breaks were considered as low. Similar levels of DNA strand breaks have been observed in similar research in the control group, meaning that this level of DNA strand breaks is considered normal [ 14 ]. The obtained results revealed the absence of significant levels of DNA damage in C. grayanus gills and digestive gland cells after 12 days of feeding on P. foraminosum , despite the fact that the active forms of DTX-1 were present at a high concentration.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The observed levels of DNA strand breaks were considered as low. Similar levels of DNA strand breaks have been observed in similar research in the control group, meaning that this level of DNA strand breaks is considered normal [ 14 ]. The obtained results revealed the absence of significant levels of DNA damage in C. grayanus gills and digestive gland cells after 12 days of feeding on P. foraminosum , despite the fact that the active forms of DTX-1 were present at a high concentration.…”
Section: Discussionsupporting
confidence: 74%
“…The role of transforming the active toxin to DTX-3 is supposed to protect bivalves from DSTs activity [ 13 ]. However, these protective mechanisms may not always be effective, as it has recently been shown that a high density of Prorocentrum lima may cause oxidative DNA damage in haemocytes of the mussel Mytilus galloprovincialis [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The choice of gill tissue as model system in the present work was motivated by previous reports indicating that gills are the part of the organism first contacted by biotoxins during HABs, experiencing substantial DNA damage , Prego-Faraldo et al 2016.…”
Section: Experimental Hab Simulationmentioning
confidence: 99%
“…During HABs, large amounts of potentially harmful biotoxins are produced and recruited into the human food chain through their accumulation by edible marine organisms , Plakas et al 2008. These biotoxins, among other relevant effects, have the ability to cause DNA damage, both in marine organisms and human consumers of contaminated shellfish , Prego-Faraldo et al 2016.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation